Anticandidal efficacy of Shikakai and rose petals in herbal denture cleanser formulation: an in vitro study - A., Sanjana; K., Sinchana; U., Mounashree; R., Nanditha B. (International Journal of Research in Medical Sciences, 2026)
Background: Chemical denture cleansers may cause irritation, discoloration, and allergic reactions in denture wearers. Herbal agents with antimicrobial properties are being explored as safer alternatives to prevent denture-associated infections such as oral candidiasis. This study aimed to develop and evaluate a natural denture cleanser using Acacia concinna (Shikakai) and Rosa spp. (rose petals). Methods: Dried plant materials were extracted using the Soxhlet extraction method and subjected to qualitative phytochemical screening. Antimicrobial activity against Candida species was assessed in vitro. The extracts were formulated into effervescent tablets for immersion-type denture cleansing. The tablets were evaluated for weight variation, hardness, friability, pH, disintegration time, and in vitro dissolution. Cleaning efficiency and anticandidal activity were also studied. Results: Phytochemical screening confirmed the presence of flavonoids, saponins, tannins, and glycosides, with Shikakai extract showing a richer phytochemical profile. Antimicrobial studies demonstrated stronger antifungal activity of Shikakai against Candida species compared to rose petal extract. The formulated tablets met acceptable quality control parameters. In vitro dissolution studies showed about 20% release within one hour and nearly 90% release within six hours. Shikakai-based formulations exhibited superior cleaning efficiency and anticandidal activity. Conclusions: Shikakai-based herbal denture cleanser tablets showed effective antifungal activity, satisfactory tablet properties, and good cleaning performance, indicating their potential as a natural alternative to synthetic denture cleansers. Further clinical studies are needed to confirm long-term safety and user acceptability.